2019
DOI: 10.1515/med-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-181a-5p regulates inflammatory response of macrophages in sepsis

Abstract: AbstractThe aim of this study was to evaluate the role of miR-181a-5p in sepsis, and to further explore the molecular mechanism. RAW 264.7 cells were stimulated with 1 μg/ml LPS for 4 hours. Firstly, qRT-PCR and ELISA was adopted to evaluate the expression of miR-181a-5p and p ro-inflammatory cytokines in RAW 264.7 macrophages a fter LPS stimulation. Results showed that pro-inflammatory cytokines and miR-181a-5p were significantly increased after LPS treatment. Then, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…miR-181a-5p was identified to regulate the inflammatory response of macrophages in acute sepsis. Specific inhibitors significantly decreased the secretion of inflammatory factors in a mouse model [ 86 ]. Leukocytes are of specific interest in the development and progression of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…miR-181a-5p was identified to regulate the inflammatory response of macrophages in acute sepsis. Specific inhibitors significantly decreased the secretion of inflammatory factors in a mouse model [ 86 ]. Leukocytes are of specific interest in the development and progression of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased miR-181a expression reduced cell apoptosis of LPS-treated lung epithelial cells by targeting Bcl-2 [ 73 ]. Earlier, miR-181a-5p was also reported to be upregulated in RAW 264.7 macrophage cells and the LPS-stimulated sepsis mice model [ 74 ]. miR-181b expression was reported to be upregulated in early sepsis and sustained in late sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo blockade of miR-181 after sepsis reduced late-sepsis mortality, improved bacterial clearance, and reduced NFI-A expression, which is responsible for myeloid differentiation during sepsis [ 75 ]. The levels of creatine (Cr), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and blood urea nitrogen (BUN) significantly decreased with the miR-181a-5p inhibitor in the serum of mice with sepsis [ 74 ]. This was in support of the GO pathway analysis performed in our studies, which also revealed that most of the DEMs in our study were significantly involved in the cellular nitrogen compound metabolic process.…”
Section: Discussionmentioning
confidence: 99%
“…These EVs also contain miRNAs (15–25 nt): miR-4652-3p, miR-4301, and miR-181a-5p with gene targets related to cell adhesion and cell communication regulation [ 13 ], suggesting that these miRNA have a role in endothelial activation and could regulate the genes implicated in the barrier and structural functions of vessels in flavivirus infection [ 13 ]. Specifically, the miR-4301 has an antiproliferative and pro-apoptotic role in cancer [ 78 , 79 , 80 ], whereas miR-181a-5p negatively regulates the inflammatory response [ 81 , 82 , 83 ] that is involved in endothelial activation during DENV infection [ 13 ]. In contrast, some cellular proteins involved in the immune response, such as C3 complement protein, metalloproteinase inhibitor (MPI), and galectin-3 (Gal-3), were found inside EVs secreted by DENV-infected macrophages, as shown in Figure 5 [ 13 ].…”
Section: The Role Of Exosomes In the Host Immune Response During Fmentioning
confidence: 99%